A Clean Strategy to Prepare Polylactide/Hydroxyapatite Bionanocomposites via Solid Mechanochemistry. Issue 5 (4th May 2017) - Hua, Zhengkun; Nie, Min; Liu, Xiang; Wang, Qi
ABSTRACT: Polylactide (PLA) chains were ruptured to generate free macroradicals terminated on the surface of hydroxyapatite (HA) by means of a strong shear stress generated via solid-state shear milling, achieving the solid grafting of PLA on HA without chemical treatment. As a result, the interfacial interaction between PLA and HA and the dispersion of HA in PLA were improved, resulting in significant promotion of the crystallization of PLA and thus PLA/HA composites with higher performance were obtained. This study opened up a new, clean and uncontaminated strategy to prepare PLA/HA bionanocomposites.